Examining Changes in Abusive Attitudes and Behaviors of Intimate Partner Violence Perpetrators through a Community-based Prevention Program. Issue 9 (21st October 2021) - Wong, Jennifer S.; Bouchard, Jessica
ABSTRACT: The current study presents a pilot evaluation of a nine-week intimate partner violence intervention program delivered in British Columbia, Canada. The Respectful Relationships program uses a response-based therapy approach and targets both male abusers who volunteer for the program as well as those who are mandated; participants are pre-screened for risk indicators and the program is co-facilitated by a male/female team. A total of 64 men enrolled across eight program cycles; 29 participants completed both pretest and posttest surveys. Quantitative and qualitative self-report outcomes focused on (a) the Abusive Behavior Inventory, (b) attitudes about abuse and behavior management, and (c) curriculum-specific content designed to assess gains in skill development. Results from the pilot investigation suggest that Respectful Relationships had little effect on rates of psychological abuse, but significantly decreased rates of physical abuse among participants. In addition, significant increases were demonstrated from pretest to posttest for both skill development and attitudinal measures. Limitations and future research are discussed.